Expression of soluble, enzymatically active, human immunodeficiency virus reverse transcriptase in Escherichia coli and analysis of mutants. - Hizi, A (1988)
We have constructed a plasmid that, when introduced into Escherichia coli, induces the synthesis of large quantities of a protein with an apparent molecular mass of 66 kDa that differs from human immunodeficiency virus (HIV) RNA-dependent DNA polymerase (deoxynucleoside-triphosphate:DNA deoxynucleotidyltransferase or reverse transcriptase, EC 2.7.7.49) only in that it has two additional amino-terminal amino acids. This protein is soluble in E. coli extracts, is active in reverse transcriptase assays, and shows inhibition profiles with dideoxy-TTP and dideoxy-GTP that are indistinguishable from the viral enzyme. The deletion of 23 amino-terminal or carboxyl-terminal amino acids or the insertion of 5 amino acids at position 143 substantially decreases the polymerizing activity of the HIV reverse transcriptase made in E. coli. The properties of a 51-kDa reverse transcriptase-related protein made in E. coli suggests that the p51 found in the virion probably does not have substantial polymerizing activity. The full-length HIV reverse transcriptase and the various mutant proteins produced in E. coli should be quite useful for structural and biochemical analyses as well as for the production of antibodies.